Antimalarial therapy selection for quinolone resistance among Escherichia coli in the absence of quinolone exposure, in tropical South America. - Ross J Davidson (Public Library of Science (PLoS), 2008)
Background Bacterial resistance to antibiotics is thought to develop only in the presence of antibiotic pressure. Here we show evidence to suggest that fluoroquinolone resistance in Escherichia coli has developed in the absence of fluoroquinolone use. Methods Over 4 years, outreach clinic attendees in one moderately remote and five very remote villages in rural Guyana were surveyed for the presence of rectal carriage of ciprofloxacin-resistant gram-negative bacilli (GNB). Drinking water was tested for the presence of resistant GNB by culture, and the presence of antibacterial agents and chloroquine by HPLC. The development of ciprofloxacin resistance in E. coli was examined after serial exposure to chloroquine. Patient and laboratory isolates of E. coli resistant to ciprofloxacin were assessed by PCR-sequencing for quinolone-resistance-determining-region (QRDR) mutations. Results In the very remote villages, 4.8% of patients carried ciprofloxacin-resistant E. coli with QRDR mutations despite no local availability of quinolones. However, there had been extensive local use of chloroquine, with higher prevalence of resistance seen in the villages shortly after a Plasmodium vivax epidemic (p<0.01). Antibacterial agents were not found in the drinking water, but chloroquine was demonstrated to be present. Chloroquine was found to inhibit the growth of E. coli in vitro. Replica plating demonstrated that 2-step QRDR mutations could be induced in E. coli in response to chloroquine. Conclusions In these remote communities, the heavy use of chloroquine to treat malaria likely selected for ciprofloxacin resistance in E. coli. This may be an important public health problem in malarious areas.